Review and outlook of 30 years of optical network development - Xiaoping ZHENG; Nan HUA (Dianxin kexue)
As the core of the information network infrastructure,optical network has an irreplaceable important role.The birth process of optical network and the important milestones in its 30 years research and development course were reviewed firstly,then the challenges and possible development trends of optical networks according to future network demands were discussed.